Different commercial technological ingredients: impact on the shelf life of refrigerated fresh sausages - Adrieli Maiandra Piccinin do Amaral; Etiene Mendes Amorim; Edson Gabriel Santana do Carmo; João Vitor Padilha dos Santos; Marlei Teresinha Canova; Paulo Atílio Dalan; Luana Bettanin; Weber da Silva Robazza; Liziane Schittler Moroni; Georgia Sehn; Darlene Cavalheiro (Ciência Animal Brasileira)
This study aimed to evaluate the effects of incorporating sodium erythorbate (PC) the absence of sodium erythorbate (NC), citric acid (CA), ascorbic acid (AA), sodium lactate (SL), potassium lactate (PL), TARI L 96 Forte (TL96 - a blend of lactic acid, dextrose, citric acid, acetic acid), and rosemary extract (RE) on the pH, TBARS values, and microbial growth of vacuum-packed fresh sausages, throughout days 1, 15, 30, 35, and 40 of storage, further assessed through mathematical modeling. Mathematical modeling revealed a relevant influence of the different technological ingredients on the final bacterial population, evidencing a reduction in growth rates, mainly in the treatment TL96. However, this trend was not corroborated by statistically significant differences in the experimental data (P > 0.05). Regarding TBARS values, the use of sodium erythorbate (PC) alone, and together with the organic acid blend (TL96) was effective in delaying lipid oxidation. The treatment CA exhibited the lower constants k1 and k2, indicating a slower acidification followed by a gradual pH recovery over time. The treatments with the most favorable results in microbiological and TBARS analyses, as well as superior performance in mathematical modeling (RE, TL96, and PL) were selected for sensory evaluation. The sensory analysis revealed no statistically significant differences among treatments, except for the flavor attribute in the treatment PL. The incorporation of TARI L96 Forte and potassium lactate into the sausage formulations contributed positively to the preservation of quality and microbiological safety of the fresh sausages during refrigerated storage.